A Greek and Arabic Lexicon (GALex) : Fascicle 3 'sl -'ly - Endress, Gerhar,; Gutas, Dimitri, (Brill's Series in Jewish Studies ;, 1994)
From the eighth to the tenth century A.D., Greek scientific and philosophical works were translated wholesale into Arabic. This activity resulted in the incorporation and reorganization of the classical heritage in the new civilization which, using Arabic, spread with Islam. A Greek and Arabic Lexicon is the first systematic attempt to present in an analytical and rationalized way our knowledge of the vocabulary of the translations. It is based on the glossaries included in text editions, both published and unpublished, and on other materials gleaned from various sources. The work is published in fascicules of 128 pages of lexical entries plus indexes of the Greek-Arabic correspondences, of Greek proper names and transliterated words, of variant Greek and Arabic passages, and of the Greek authors cited in the context passages. From the second fascicule onwards the indexes are cumulative. A Greek and Arabic Lexicon is an indispensable reference tool for the study and understanding of Arabic scientific and philosophical language and literature. It facilitates the preparation of future editions of Arabic texts translated directly from the Greek, as well as of works originally composed in Arabic but based on the translations. It contributes to our knowledge of the vocabulary and syntax of Classical and Middle Arabic, of the thought and methods of the translators and of the nature of the translation activity into Arabic methods of the translators and of the nature of the translation activity into Arabic as a whole, and of the way a new vocabulary may develop in an existing language. Moreover, the Greek-Arabic glossary in general and the index of variant Greek passages in particular will assist in future editions of the Greek text of the works translated into Arabic. These provide information, in a way that can be used by classical scholars who do not know Arabic, on the readings of the manuscripts which were used by the Arab translators and which antedate by more than two centuries the Greek manuscripts actually extant. The work further contributes to our knowledge of the vocabulary of Classical and Middle Greek and of the reception and reading of classical Greek works in late antiquity and pre-Photian Byzantine literature.